Fibroblast growth factor 15/19 (FGF15/19) protects from diet-induced hepatic steatosis: development of an FGF19-based chimeric molecule to promote fatty liver regeneration. Issue 10 (24th January 2017) - Alvarez-Sola, Gloria; Uriarte, Iker; Latasa, M Ujue; Fernandez-Barrena, Maite G; Urtasun, Raquel; Elizalde, Maria; Barcena-Varela, Marina; Jiménez, Maddalen; Chang, Haisul C; Barbero, Roberto; Catalán, Victoria; Rodríguez, Amaia; et al.
Abstract : Objective: Fibroblast growth factor 15/19 (FGF15/19), an enterokine that regulates synthesis of hepatic bile acids (BA), has been proposed to influence fat metabolism. Without FGF15/19, mouse liver regeneration after partial hepatectomy (PH) is severely impaired. We studied the role of FGF15/19 in response to a high fat diet (HFD) and its regulation by saturated fatty acids. We developed a fusion molecule encompassing FGF19 and apolipoprotein A-I, termed Fibapo, and evaluated its pharmacological properties in fatty liver regeneration. Design: Fgf15 −/− mice were fed a HFD. Liver fat and the expression of fat metabolism and endoplasmic reticulum (ER) stress-related genes were measured. Influence of palmitic acid (PA) on FGF15/19 expression was determined in mice and in human liver cell lines. In vivo half-life and biological activity of Fibapo and FGF19 were compared. Hepatoprotective and proregenerative activities of Fibapo were evaluated in obese db/db mice undergoing PH. Results: Hepatosteatosis and ER stress were exacerbated in HFD-fed Fgf15 −/− mice. Hepatic expression of Pparγ2 was elevated in Fgf15 −/− mice, being reversed by FGF19 treatment. PA induced FGF15/19 expression in mouse ileum and human liver cells, and FGF19 protected from PA-mediated ER stress and cytotoxicity. Fibapo reduced liver BA and lipid accumulation, inhibited ER stress and showed enhanced half-life. Fibapo provided increased db/db mice survival and improved regeneration upon PH. Conclusions: FGF15/19 is essential for hepatic metabolic adaptation to dietary fat being a physiological regulator of Pparγ2 expression . Perioperative administration of Fibapo improves fatty liver regeneration.